24.6k views
4 votes
The answer simplifying this problem please. With positive exponents only.

The answer simplifying this problem please. With positive exponents only.-example-1
User SharpBarb
by
5.7k points

1 Answer

4 votes

Answer:

1/(xy²)

Step-by-step explanation:

The given expression is


(x^(-4)y^(-2)z^7)/(x^(-3)z^7)

To simplify the expression, we will use the following properties


\begin{gathered} (x^a)/(x^b)=x^(a-b) \\ x^(-a)=(1)/(x^a) \end{gathered}

So, we need to apply the first property for x and z to get:


\begin{gathered} (x^(-4)y^(-2)z^7)/(x^(-3)z^7)=x^(-4-(-3))y^(-2)z^(7-7)^{} \\ ^{}=x^(-4+3)y^(-2)z^0 \\ ^{}=x^(-1)y^(-2)\cdot1 \\ =x^(-1)y^(-2) \end{gathered}

Because any number to the power of 0 is equal to 1. Then, apply the second property to get


(1)/(x^1y^2)=(1)/(xy^2)

Therefore, the answer is 1/(xy²)

User Sitram
by
5.8k points